Menavigasi Era Disrupsi: Menuju Transformasi Manajemen Mutu Pendidikan Islam yang Adaptif dan Inovatif - Sofiah, Muti Atus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the implications of the transformation of Adaptive and Innovative Islamic Education Quality Management in the era of disruption. This research uses a qualitative method with a case study approach at the Ulya Muadalah Education Unit (SPM) school institution at the Darussalam Blokagung Islamic Boarding School. Data collection techniques were collected through in-depth interviews, participatory observation, and document analysis, with the main informants consisting of principals, teachers, administrative staff and students. While data analysis used thematic analysis method with data coding to identify key themes that emerged from interviews, observations, and document analysis. The results showed that the Transformation of Adaptive and innovative islamic education quality management in the era of disruption included collaboration and cooperation networks, teacher professional development and 21st Century Skills-Based curriculum development. collaboration and cooperation networks between the Ulya Muadalah Education Unit (SPM) with madrasah diniyyah Al Amiriyyah, SPM Wustho, and Ma'had Aly institutions have proven to be an effective strategy in improving the quality of education and academic competence of students while teacher professional development is carried out with activities such as consortium, shawir and Batsul Masail